2013
DOI: 10.1111/hpb.12041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection and hepatocellular carcinoma in liver transplantation: a 20‐year experience

Abstract: HCV patients had lower survival post-LT. HCC alone had no impact on survival. Patient survival decreased in the HCC+/HCV+ group and this appears to be as a consequence of HCV recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Even after adjusting for multiple potential contributing factors in the multivariate model, the survival disadvantage associated with HCV and HCC persisted. Lower post‐LT survival among patients with HCV has been attributed to the high rate of HCV recurrence among this cohort . However, this survival difference appears to be limited to patients without HCC, as our subanalyses of patients with HCC demonstrated no significant difference in post‐LT five‐yr patient or graft survivals by etiology of liver disease.…”
Section: Discussionmentioning
confidence: 62%
“…Even after adjusting for multiple potential contributing factors in the multivariate model, the survival disadvantage associated with HCV and HCC persisted. Lower post‐LT survival among patients with HCV has been attributed to the high rate of HCV recurrence among this cohort . However, this survival difference appears to be limited to patients without HCC, as our subanalyses of patients with HCC demonstrated no significant difference in post‐LT five‐yr patient or graft survivals by etiology of liver disease.…”
Section: Discussionmentioning
confidence: 62%
“…HCV infection predicted only shorter post‐LT survival for non‐HCC patients. Prior studies noted the same lack of an association between HCV and post‐LT outcomes in patients undergoing transplantation for HCC . We theorize that HCV reinfection after LT primarily imparts a post‐LT mortality risk by increasing the risk of recurrent cirrhosis rather than recurrent HCC.…”
Section: Discussionmentioning
confidence: 74%
“…Prior studies noted the same lack of an association between HCV and post-LT outcomes in patients undergoing transplantation for HCC. [40][41][42] We theorize that HCV reinfection after LT primarily imparts a post-LT mortality risk by increasing the risk of recurrent cirrhosis rather than recurrent HCC. Because recurrent cirrhosis and recurrent HCC are competing risks in patients undergoing transplantation with both HCV and HCC (HCC recurrence does not require HCV-related graft fibrosis), it follows that HCV would be a weaker predictor of post-LT survival in patients with both HCC and HCV versus HCV alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HCV eradication in the pre-LT setting prevents recurrence of liver infection (45) and has been associated with higher survival in patients transplanted for HCC. (46) Additionally, Martini et al recently showed that reaching HCV RNA undetectability in the pre-or peri-LT setting could lower the risk of early allograft dysfunction in HCV-positive recipients. (47) This finding, together with our results, should further encourage clinicians to treat HCV patients as early as possible, especially in HCC patients awaiting LT who may be more likely to receive grafts from marginal donors with the consequent higher risk of post-LT complications.…”
Section: Included 1 Cohort Of Hcc Lt Recipients Subsequently Treated mentioning
confidence: 99%